Comparison of Maximum Phonation Duration and S/Z Ratio in Individuals with Asthma, Tuberculosis and Clinically Normal Voice - Shrestha, Susmita; Adhikari, Anil Kumar (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: The ability of a person to phonate a sound gets affected in different laryngeal and respiratory pathology which can be measured by the help of two measure called as Maximum Phonation Duration (MPD) and S/Z ratio that  helps to assess the efficiency of  respiratory and phonatory system. The aim of this study is to measure the MPD and S/Z ratio in Normal, Tuberculosis and Asthma group patient.Methods: The participant included Normal, Asthma and Tuberculosis patient where the recording was made in a quiet room with the help of PRAAT software and the participant were asked to sustain phonation of sound on single breath. Analysis was done with helps of SPSS version 25.0.Results: There was a significant difference noted in MPD of /a/, /i/, /u/ sound between control and experimental group. MPD were significantly shorter in Asthma and Tuberculosis group compared to Normal group with no significant difference in S/Z ratio.Conclusions: Maximum Phonation Duration is more reduced in Asthma and Tuberculosis patient compared to Normal group which indicate Asthma and Tuberculosis patient has to put more effort to phonate a sound.